The Influence of Company Size, Tax Planning, and Deferred Tax Assets on Non-cyclical Consumer Company Earning Management - Dea Nurita, Alvina; Anugerahini Putri, Fitra; Didin Kartika, Ratih; Dwi Mahaswari, Lintang; Devie Savana Putri, Mehra; Amrulloh, Amri (Inovasi Analisis Data, 2024)
This study examines the influence of firm size, tax planning, and deferred tax assets on the manipulation of earnings in non-cyclical consumer companies that are publicly traded on the Indonesia Stock Exchange. The primary goal is to examine the connections between these variables and their combined impact on earnings manipulation. The study selects 64 organizations through purposive sampling and uses associative quantitative research methods to assess secondary data from their financial reports. The analysis indicates that company is no significant impact on earnings management from company size, tax planning, or deferred tax assets, whether examined individually or collectively. This indicates that larger corporations, although more widely known and subject to more oversight, do not participate in profit manipulation to a greater extent than smaller enterprises. Similarly, tax planning and deferred tax assets are primarily used to enhance fiscal efficiency rather than manipulate results. The low coefficient of determination suggests that there are other elements, not considered in this study, that have a greater impact on earnings management. In line with previous research, these results highlight the fact that deferred tax assets, firm size, and tax planning are not the main factors influencing earnings management in Indonesian non-cyclical consumer companies. More variables that add to a more thorough understanding of the factors influencing earnings management should be found through longer-term and larger sample sizes in future studies.